Contemporary Da'wah Based on Cosmopolitan Islam - Maftukhin Maftukhin (Universitas Islam Tribakti Lirboyo Kediri, 2023)
The development of Islam is currently experiencing relatively rapid development, mainly supported by technological developments. Islam views technological developments as opportunities for effective da'wah. In addition to facilitating the da'wah process, the existence of technology makes preachers more able to reach Mad'u from all walks of life. Da'i preaches with da'wah material that is readily accepted by the community by adjusting the geographic location, psychology, and intellectual capacity of Mad'u. The research method used in this article was a qualitative method using a literature approach. The result of this article is the da'wah process of contemporary preachers who carry out cosmopolitan Islamic da'wah by upholding the value of tolerance so that all levels of society can accept it. Such da'wah will provide a complex understanding for Mad'u to accept each other's differences within the framework of the Indonesian state.